The relationship between conflict management styles and employees performance at Universiti Malaysia Kelantan (UMK) Kampus Kota / Asmira Aziz - Aziz, Asmira (2015)
Conflict is a something that cannot be separated from people's life. It is also viewed as a phenomenon that requires management. This research was conducted to explore and to describe the types of conflict that affect the employee performance of Universiti Malaysia Kelantan (UMK) Kampus Kota and to identify the styles used by employees at Universiti Malaysia Kelantan (UMK) Kampus Kota to manage conflict arise in the organization. It also conducted to find out the relationship between conflict management styles and employees performance at Universiti Malaysia Kelantan (UMK) Kampus Kota. Data has been collected from seven different units in Universiti Malaysia Kelantan (UMK) Kampus Kota by using questionnaires. The collected data has been analyzed using descriptive statistics and distribution graph. Finding showed that the most type of conflict occurred at Universiti Malaysia Kelantan (UMK) Kampus Kota was interpersonal conflict. Interpersonal conflict exists when disagreement happened between two interdependent people who see that they have incompatible goals. Besides that, finding showed that the most style used at Universiti Malaysia Kelantan (UMK) Kampus Kota in handling conflicts was collaborating. From the finding of this research, it can be concluded that there is significant relationship between conflict management styles and employees performance at Universiti Malaysia Kelantan (UMK) Kampus Kota. Based on the finding of this research, it is recommended for manager at the organization to send employees to the training for interpersonal skills and to develop emotional intelligence in order to resolve conflict existed in the organization.